Biodiversitas Vegetasi Mangrove di Kecamatan Concong Kabupaten Indragiri Hilir Provinsi Riau - Wirdati Irma; Any Tri Atmaja; Muh. Aris Marfa’i (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Mangrove ecosystems have a vital role in environmental sustainability, especially in coastal areas. It is necessary to calculate the biodiversity of mangrove vegetation in Concong District, Indragiri Hilir Regency. The aim is to find out the types and levels of biodiversity of mangrove vegetation in Concong District, Indragiri Hilir Regency, Riau Province. The method used in the survey is the transect plot. The research sample was taken from 5 (five) villages and 1 (one) village in Concong District. Each village and village were made of 2 transects. Each transect is made of 3 plots. The plot size used is 20x20 meters at the tree level. The total number of plots was 36 plots. Data were analyzed using the Biodiversity Index using the Shannon Winner formula. The results obtained 14 types of mangrove vegetation into six families, namely Avicenniaceae, Rhizophoraceae, Euphorbiaceae, Arecaceae, Sonneratiaceae, and Meliaceae. Six species out of the 14 total species found in Concong District are dominated by the Rhizophotaceae family. The biodiversity index value obtained from the distribution of mangrove vegetation in five villages and one kelurahan is 2.03. The resulting biodiversity index value indicates the level of biodiversity of mangrove vegetation in Concong District is in the medium category. This condition is possible because there has been damage and exploitation of mangrove vegetation continuously without proper management.